Evaluasi Pengetahuan Pengobatan Penyakit Diare pada Ibu Pemberdayaan dan Kesejahteraan Keluarga di Desa Karanganyar Kubu Karangasem Bali - Luh Anggi Distya Pratiwi; Gusti Ayu Dinda Pradnya Swari Wijaya (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2026)
Diarrhea is a significant health issue that leads to a lot of illness and death, ranking third in Indonesia. The causes of diarrhea include inadequate environmental cleanliness, contaminated water sources, and insufficient knowledge in the community. When the community lacks knowledge, it can result in unsuccessful treatment outcomes. This ponder pointed to analyze how mother strengthening and family prosperity information influence loose bowels treatment in Karanganyar Kubu Karangasem Town, Bali. This think about executed a Pre Exploratory Plan, especially utilizing a one gather pre-post test arrange. The subjects of this ponder were moms chosen based on foreordained consideration and avoidance rules, centering on strengthening and family wellbeing. Data to assess the advancement of knowledge was gathered using questionnaires during the pretest, posttest I, and posttest II phases. Members included moms who were portion of family welfare activities in Karanganyar Kubu Karangasem town in Bali. Speculation testing was carried out to compare the comes about from the pretest to posttest I p <0.001, pretest to posttest II p <0.001, and posttest I to posttest II p <0.001, illustrating a noteworthy improvement in information after experiencing instruction through the CBIA strategy.